Imageless Navigation Accurately Measures Component Orientation during Total Hip Arthroplasty: A Comparison with Postoperative Radiographs - Paprosky, Wayne G.; Muir, Jeffrey M.; Sostak, Jennifer R. (The Journal of Hip Surgery, 2019)
Accurate placement of acetabular components during total hip arthroplasty (THA) is paramount in ensuring long-term stability. Current methods for monitoring cup position and leg length intraoperatively are lacking due to susceptibility to inaccuracy or prohibitive cost. The purpose of this study was to evaluate the ability of an imageless surgical navigation tool to accurately measure acetabular cup inclination and leg length differential during THA. The authors retrospectively reviewed the medical records of patients who underwent primary or revision THA (posterolateral approach) at their facility with the assistance of computer-assisted navigation between February 2016 and March 2017. Pre- and postoperative radiographs were analyzed for leg length discrepancies and acetabular cup inclination. Radiographic values were compared with intraoperative values provided by the surgical navigation tool. The mean difference between inclination as measured from radiographs (44.4 ± 5.9 degrees) and navigation (43.0 ± 4.4 degrees) was −1.4 ± 4.6 degrees (mean absolute difference: 3.8 ± 2.8 degrees). Seventy-seven percent (48/62) of navigation measurements were within 5 degrees of radiographs. The mean difference between radiographic (7.39 ± 5.67 mm) and navigation (7.44 ± 4.81 mm) measurements of leg length differential was 0.29 ± 4.20 mm (mean absolute difference: 3.20 ± 2.69 mm). Navigation tool measurements were within 5 mm of radiographic values in 85% (39/46) of cases. At 90 days, idiopathic dislocation requiring revision surgery occurred in one patient (1.2%) with one additional patient (1.2%) requiring revision surgery due to a traumatic injury (fall). Computer-assisted navigation provided accurate intraoperative data regarding inclination and changes in leg length and was associated with a low rate of dislocation and revision surgery at 90-day follow-up.
Keywords: total hip arthroplasty; cup position; computer-assisted navigation; leg length